(untitled) (International Journal of Engineering and Computer Science, 2018)
Cloud computing is a current research area that provides elastic and flexible computing resources to best fit the today’s business needs. In place of several advantages offered by cloud computing environments, it deals with the major roadblocks in its way of growth. The major roadblocks considered are found as security and secrecy of data along with the trust on cloud service providers (CSP). This paper tries to find out the trust parameters which could help in increasing trust of users on the service providers and helping to encourage the use of cloud computing among users at large. This paper proposes a new user trust model that finds out the trust parameters that make strong impact on users’ trust in the cloud environment. The model helps the cloud service users (CSUs) to establish trust in the cloud service providers’ (CSPs) for availing their services. Also the CSPs can refer the model to enhance their services for getting more trust among CSUs.